2022
DOI: 10.1080/13538322.2022.2123267
|View full text |Cite
|
Sign up to set email alerts
|

Quality work in higher education: a multi-stakeholder study

Abstract: Quality in higher education has been at the top of the political agenda for years, motivating discussion of how to define quality and how standards and assessment can promote quality. However, the literature tends to overlook the processes and practices constituting 'every-day' quality. To improve quality, it is important to know how quality is perceived and enacted by the key stakeholders, namely the students, teachers, administrative staff and managers. Informed by the findings of a survey, this article aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The research findings published by Borg et al (2019) indicate that it is crucial for educational institutions to incorporate stakeholder feedback into the development of curriculum in order to design courses that are both workforceready and boost graduates' employability. Bloch et al (2023) emphasize the significance of stakeholder engagement in elevating the level of education, pointing out that engaging with a range of stakeholders provides enlightening perspectives on quality standards and areas that may be continually enhanced. Furthermore, the research results published by Yami et al (2018) and Sartas et al (2019) demonstrated the significance of stakeholder participation in shaping policy decisions and how this helps to develop more inclusive and effective policy frameworks that meet the diverse needs of stakeholders in education.…”
Section: Successful Strategiesmentioning
confidence: 99%
“…The research findings published by Borg et al (2019) indicate that it is crucial for educational institutions to incorporate stakeholder feedback into the development of curriculum in order to design courses that are both workforceready and boost graduates' employability. Bloch et al (2023) emphasize the significance of stakeholder engagement in elevating the level of education, pointing out that engaging with a range of stakeholders provides enlightening perspectives on quality standards and areas that may be continually enhanced. Furthermore, the research results published by Yami et al (2018) and Sartas et al (2019) demonstrated the significance of stakeholder participation in shaping policy decisions and how this helps to develop more inclusive and effective policy frameworks that meet the diverse needs of stakeholders in education.…”
Section: Successful Strategiesmentioning
confidence: 99%